Tribological effect of thermal energy on TIG arc surfacing techniques for surface modification of stainless steel - Paijan, Lailatul Harina; Shamsuri, Alin Qistina; Mohd Rosli, Zulkifli; Mamat, Mohd Fauzi (Malaysian Tribology Society, 2025)
TIG (tungsten inert gas) torch surface modification is a unique process that can produce the surface alloying on a work surface and effectively improve surface hardness while altering the tribological behaviors. The significance of this work is to examine the influence of thermal energy on the surface characteristic of 2205 duplex stainless steel samples. The thermal energy varied from 0.48 to 1.440 KJ/mm. The surface hardness and microstructure features of the tribological properties of the materials were examined. Results indicate that, as thermal energy increases, the hardness value increases, thereby resulting in an increase of tribological properties. However, at higher thermal energy of 1.440 KJ/mm, the modified surface exhibits cracking in the melt layer. The microstructure transformed into different populations of dendritic structures. The best thermal energy obtained was 0.768 KJ/mm that resulted in the lowest wear rate of 3.0 x 10-4 mm3/Nm and friction coefficient of 0.43. High hardness of the surface modification and increased tribological behavior were linked to higher levels of arc energy during TIG melting process.